Variation in Rooting Response in ten Provenances of Azadirachta indica A. Juss - Gera, Mohit; Gera, Neelu; Meena, S. L.; Singh, Tribhuven (Indian Forester, 1998)
The rooting response of ten indigenous provenances of Azadirachta indica under the effect of different treatments viz., IAA, IBA and Thiamine was studied in a factorial RBD experiment. Signifiant variations in almost all parameters were recorded among the different provenances, treatments and their interactions. The treatment IBA 1000 ppm performed the best for all the parameters studied. The treatment increased rooting by 85.5%, number of roots per cuttings by 240.8%, maximum root length by 68% and root dry wt. by 218.7% over control. The provenance Mandore, Rajasthan (P9) showed overall best rooting response with 64.17% rooting, 9.64 number of roots per cutting, 6.15 em maximum root length and 0.075% gmIcutting root dry wt. The interaction of provenance Midnapur, West Bengal (P5) with treatment IBA 1000 ppm (T3) gave best results in respect of number of roots per cutting (17.67), maximum root length (7.61 cm) and root dry weight (0.163 gm/cutting). However, the provenance Dodaballapur, Karnataka (P10) with treatment IBA 1000 ppm (T3) gave the maximum rooting (96.67%). The findings indicate that it is desirable to include rooting ability of a provenance as an important criterion for its selection and evaluation.